What Kind of Content Knowledge do Secondary Mathematics Teachers Need?: A Conceptualization Taking into Account Academic and School Mathematics Welches Fachwissen benötigen Mathematiklehrkräfte der Sekundarstufe?: Eine Konzeptualisierung, die sowohl universitäre als auch schulische Mathematik berücksichtigt - Dreher, Anika; Lindmeier, Anke; Heinze, Aiso; Niemand, Carolin (Journal für Mathematik-Didaktik, 2018)
The discrepancy between school and academic mathematics as well as the resulting problems for secondary mathematics teachers’ content knowledge (CK) have been well known since Felix Klein pointed out the problem of so-called double discontinuity. However, even today, the field of mathematics education has no clear answer to the question as to what kind of profession-specific CK secondary mathematics teachers need and should be taught during the course of their teacher education. Hence, a model of professional CK for teaching secondary mathematics is required which takes into account the discrepancy between the academic mathematics that teachers learn at university and the school mathematics they teach in school. In order to characterize such a profession-specific CK, this theoretical paper traces and integrates different approaches to bridge this gap. Consequently, a construct called school-related content knowledge (SRCK) is introduced, which describes a profession-specific CK for teaching secondary mathematics concerning interrelations between academic and school mathematics. The conceptualization of this construct encompasses three facets that are illustrated by means of a corresponding operationalization. The distinction of SRCK from the construct of specialized content knowledge is discussed, as are emerging research questions.
CRIS-Team Scopus Importer:2024-10-02
Keywords: A40; B50; D20; Elementary mathematics from a higher standpoint; Mathematics teacher education; Profession-specific content knowledge; Professional knowledge; School-related content knowledge